تطبيق لعبة العجلة الدوارة على الأساس الرقمي لترقية تعليم المفردات (البحث التجريبى لطلاب الفصل السابع بالمدرسة الثانوية الإسلامية الأهلية الغزالية جومبانج) - Ode Rahman Arfan; Mu'ad Mu'ad (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
Learning Arabic at the Sanawiya madrasah level tends to be less popular due to the lack of media in the learning process. One example is Arabic vocabulary lessons, which are lessons that are considered boring. This research aims to provide variations in learning Arabic vocabulary by using a spinning wheel game, with the aim of increasing students' understanding of vocabulary. Therefore, researchers conducted pre-experimental research on the application of a digital-based spinning wheel game to improve vocabulary learning for class VII students at Madrasah Ṣānawiyyah Ghazaliyya Jombang. The subjects of this research were 30 class VII students. In this study, researchers used the one-group pretest-posttest method. At the initial meeting, the researcher conducted a pretest, then gave treatment with a spinning wheel game, and then conducted a posttest. The results obtained showed that there was a significant increase in learning outcomes before and after carrying out the treatment. In the initial test, students obtained an average score of 57.50, and in the final test after treatment, students obtained an average score of 84.50. So descriptively, the posttest value is better than the pretest value, with a significance level of difference between the two values of 0.000 <0.05 (a sig value of 0.000 is less than 0.05). This means that the use of learning media with spinning wheel games in learning Arabic has a good influence on students. In other words, the spinning wheel game can improve students' learning of Arabic vocabulary.